2015
DOI: 10.18632/oncotarget.3310
|View full text |Cite
|
Sign up to set email alerts
|

EBNA3C regulates p53 through induction of Aurora kinase B

Abstract: In multicellular organisms p53 maintains genomic integrity through activation of DNA repair, and apoptosis. EBNA3C can down regulate p53 transcriptional activity. Aurora kinase (AK) B phosphorylates p53, which leads to degradation of p53. Aberrant expression of AK-B is a hallmark of numerous human cancers. Therefore changes in the activities of p53 due to AK-B and EBNA3C expression is important for understanding EBV-mediated cell transformation. Here we show that the activities of p53 and its homolog p73 are d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 57 publications
0
26
0
Order By: Relevance
“…Epstein Barr-Nuclear antigen EBNA-3C is expressed in latency stage and can transform primary B lymphocytes to lymphoblastoid cell lines (Whitehurst et al, 2015). In the course of transformation both EBNA3C targets several tumor suppressors like p53, p73 and pRB through a mechanism of phosphorylation and ubiquitination (Jha et al, 2015c). it was found EBNA3C has a specific interaction with IRF4 which results in enhanced stabilization of IRF4 (Banerjee et al, 2013).…”
Section: Introductionmentioning
confidence: 96%
“…Epstein Barr-Nuclear antigen EBNA-3C is expressed in latency stage and can transform primary B lymphocytes to lymphoblastoid cell lines (Whitehurst et al, 2015). In the course of transformation both EBNA3C targets several tumor suppressors like p53, p73 and pRB through a mechanism of phosphorylation and ubiquitination (Jha et al, 2015c). it was found EBNA3C has a specific interaction with IRF4 which results in enhanced stabilization of IRF4 (Banerjee et al, 2013).…”
Section: Introductionmentioning
confidence: 96%
“…However, only EBNA3A and EBNA3C are essential for viral transformation of B-lymphocytes, and all appear to significantly contribute to maintaining the viability of transformed cells, suggesting an important role in oncogenesis (Tomkinson et al, 1993). EBNA3C has been reported to interact with many cellular factors (Robertson et al, 1995; Choudhuri et al, 2007; Saha et al, 2011, 2015; Banerjee et al, 2013, 2014; Jha et al, 2013a, 2014, 2015a,b,c). One of these cellular antigens is RBP-JK, which binds to all the EBNA3 proteins (Robertson et al, 1995, 1996).…”
Section: Ebv Nuclear Antigens and Their Contribution To Oncogenesismentioning
confidence: 99%
“…The available database included cellular players that are significantly associated ( p -value is ∼10 -13 ) with transformation and proliferation of tumor cell lines ( p -value is ∼10 -12 ) ( Figure 2 ). Our lab and others have demonstrated that EBNA1, EBNA2, EBNA3C, and LMP1 are potent EBV antigens associated with a number of transcription factors including E2F1, Tp73, MDM2, Tp53, IRF4, Myc, HDAC1, and GMNN (Robertson et al, 1995, 1996; Kaiser et al, 1999; Ma et al, 2000; Plaxco et al, 2000; Zhou et al, 2000, 2005; Knight et al, 2005; Liu et al, 2005; Saridakis et al, 2005; Choudhuri et al, 2007; Ding et al, 2007; Chau et al, 2008; Allday, 2009; Forte and Luftig, 2009; Borestrom et al, 2012; Frappier, 2012a; Accardi et al, 2013; Banerjee et al, 2013; Tursiella et al, 2014; Jha et al, 2015b,c; Saha et al, 2015), kinases including Aurora Kinase B, Pim1, GSK3B (Saha et al, 2011; Jha et al, 2013a; Banerjee et al, 2014; Edwards et al, 2015), and forms complexes with cellular factors whcih includes the tumor suppressor and oncoproteins, Rb, Skp2, and CyclinD (Arvanitakis et al, 1995; Ruf and Sample, 1999; Prathapam et al, 2002; Knight et al, 2005; Choudhuri et al, 2007; Kang et al, 2011; Saha and Robertson, 2011; Saha et al, 2011, 2015; Sun et al, 2015; Figure 2 ). Cell transformation is regulated through a broad range of interacting partners including Rb, E2F1, Aurora Kinase B, Tp73, Mdm2, Pim1, Tp53, IRF4, Skp2, and Myc (Halazonetis and Kandil, 1991; Lahoz et al, 1994; Hoang et al, 1995; Pirollo et al, 1997; De Laurenzi et al, 1998; Givol et al, 1998; Mochizuki et al, 1999; Lin et al, 2000; Gstaiger et al, 2001; Kanda et al, 2005; Zhang et al, 2005; Xu et al, 2011).…”
Section: Ebv Nuclear Antigens and Their Contribution To Oncogenesismentioning
confidence: 99%
See 2 more Smart Citations